Finishing properties of Acacia mangium - Rodzali, Muhamad Saiful (2018)
The paper discusses the effect of bleaching agent and concentration on the wettability of Acacia mangium and effect of finishing system on finishing properties of Acacia mangium. The study consists of two phases. Contact angle was calculated in the first phase. Adhesion test and impact test were conducted in the second phase. The wettability was studied to assess the effects on the wettability of Acacia mangium surface bleaching agents i.e. sodium hydroxide, methanol and control. There were seven levels of concentration of bleaching agent which 2%, 4%, 6%, 8%, 10%, 12% and 14%. It seems that the concentration of bleaching agent affect the wettability of Acacia mangium. Methanol was the only bleaching agent that gave effects on the samples. The finishing properties of Acacia mangium was tested at the second phase involve three type of coating system which are acid catalyst (AC), nitrocellulose (NC), and polyurethane (PU). Adhesion test (cross-cut) was conducted based on BS: EN ISO 2409:2013 and impact test based on BS 3962: PART 6:1980.